Catalytic hydroboration of carbonyl compounds and pyridine derivatives with the NHC-parent silyliumylidene cation - Lee, Jiawen (Nanyang Technological University, 2020)
This thesis describes the catalytic hydroboration of carbonyl compounds and pyridine derivatives mediated by an N-heterocyclic carbene-parent silyliumylidene cation to give the corresponding borate esters and N-boryl-1,4-dihydropyridine products in good yield, respectively. The catalysis also shows chemo- and regioselectivity. The mechanism was proposed and investigated by DFT calculations.